Has Phytodetritus Processing by an Abyssal Soft-Sediment Community Recovered 26 Years after an Experimental Disturbance? - Stratmann, Tanja; Mevenkamp, Lisa; Sweetman, Andrew K.; Vanreusel, Ann; van Oevelen, Dick (Frontiers in Marine Science, 2018)
The potential harvest of polymetallic nodules will heavily impact the abyssal, soft sediment ecosystem by removing sediment, hard substrate and associated fauna inside mined areas. It is therefore important to know whether the ecosystem can recover from this disturbance and if so at which rate. The first objective of this study was to measure recovery of phytodetritus processing by the benthic food web from a sediment disturbance experiment in 1989. The second objective was to determine the role of holothurians in the uptake of fresh phytodetritus by the benthic food web. To meet both objectives, large benthic incubation chambers (CUBEs; 50 × 50 × 50 cm) were deployed inside plough tracks (with and without holothurian presence) and at a reference site (holothurian presence, only) at 4100 m water depth. Shortly after deployment, 13C- and 15N-labelled phytodetritus was injected in the incubation chambers and during the subsequent three-day incubation period, water samples were taken five times to measure the production of 13C-dissolved inorganic carbon over time. At the end of the incubation, holothurians and sediment samples were taken to determine biomass, densities and incorporation of 13C and 15N into bacteria, nematodes, macrofauna and holothurians. For the first objective, the results showed that biomass of bacteria, nematodes and macrofauna did not differ between reference sites and plough track sites when holothurians were present. Additionally, meiofauna and macrofauna taxonomic composition was not significantly different between the sites. In contrast, total 13C uptake by bacteria, nematodes and holothurians was significantly lower at plough track sites compared to reference sites, though the number of replicates was low. This result suggests that important ecosystem functions such as organic matter processing has not fully recovered from the disturbance that occurred in 1989. For the second objective, the analysis indicated that holothurians incorporated 2.16×10-3 mmol labile phytodetritus C m-2 d-1 into their biomass, which is one order of magnitude less as compared to bacteria, but 1.3 times higher than macrofauna and one order of magnitude higher than nematodes. Additionally, holothurians incorporated more phytodetritus carbon per unit biomass than macrofauna and meiofauna, suggesting a size-dependence in phytodetritus carbon uptake.